ODONTALGIA IN MAXILLOFACIAL REGION - A.K. Nikolishin; O.V. Rybalov; I.A. Korolenko (Український стоматологічний альманах)
Odontogenic lesions of the trigeminal nerve branch system (neuritis, neuralgia, odontalgia) that tend to have a long chronic course are more common in middle and old age. They can be caused by defects in the treatment and restoration of teeth, inflammatory and traumatic processes in the maxillofacial region, and others. The dentist should distinguish between the terms: "odontalgia" and "odontogenic trigeminal neuralgia". Odontogenic neuralgias do not disappear after the elimination of the main odontogenic pathological focus. If after the sanitation of the oral cavity pain disappears, then we are talking about odontalgia.